THE OBG NURSE’S ROLE IN REPRODUCTIVE JUSTICE: ADVOCATING FOR EQUITABLE ACCESS TO REPRODUCTIVE HEALTHCARE SERVICES - Dr.Meenu Paul (EPRA International Journal of Multidisciplinary Research (IJMR), 2024)
Reproductive justice is a fundamental human right that extends beyond mere reproductive rights, encompassing broader social, economic, and political factors that affect individuals’ ability to make reproductive choices freely and without coercion. Obstetric and Gynecologic (OBG) nurses are at the forefront of advancing reproductive justice principles within healthcare settings. This review aims to explore the concept of reproductive justice and its implications for OBG nursing practice. It delves into the critical role OBG nurses play in advocating for equitable access to reproductive healthcare services, including contraception and abortion care. By promoting policies, providing education, offering support, and addressing stigma, OBG nurses contribute significantly to healthcare equity and patient autonomy.